Facile synthesis of Ru-decorated Pt cubes and icosahedra as highly active electrocatalysts for methanol oxidation. Issue 25 (14th June 2016) - Lin, Zhuoqing; Chen, Wenlong; Jiang, Ying; Bian, Ting; Zhang, Hui; Wu, Jianbo; Wang, Yong; Yang, Deren
Abstract : Ru-decorated Pt bimetallic cubes and icosahedra were generated in a one-pot reaction and the icosahedra exhibited substantially enhanced properties towards methanol oxidation. Abstract : PtRu bimetallic particles are well-known commercial catalysts with promising performance for methanol oxidation. However, shape-controlled synthesis of PtRu bimetallic nanocrystals, especially for the platonic structures with 100 ( e.g., cubes) or 111 facets ( e.g., icosahedra) exposed towards catalysis, has met only limited success due to the different crystal structures of Pt and Ru. Here we report a facile approach to the synthesis of Ru decorated Pt bimetallic cubes and icosahedra in a mixed solvent. We found that the cubes were formed in the solvent containing N, N -dimethylmethanamide (DMF) and oleylamine (OAm) possibly due to the selective adsorption of CO on Pt100 arising from the decomposition of DMF catalyzed by a Ru salt precursor. When hexadecane was added into the aforementioned solvent, the synthesis became a two-phase interfacial reaction due to the large difference in solvent polarity, thereby retarding the reaction kinetics and promoting the formation of the icosahedra with the composition similar to the cubes. When evaluated as catalysts towards methanol oxidation, the Ru decorated Pt icosahedra showed much better performance in terms of specific and mass activity relative to the corresponding cubes. Specifically, the Ru decorated Pt bimetallic icosahedra achieved a specific activity of 0.76 mA cm −2 and mass activity of 74.43 mA mgPt −1, which is ∼6.7 and 2.2 times as high as those of the carbon supported Pt7 Ru nanoparticles, respectively. This enhancement can be attributed to a combination of twin-induced strain and facet effects.